Financial Technology and Managerial Capabilities to Improve Financial Performance: Is Technological Capital Important? - Dwi Ekasari Harmadji; Klemens Mere (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/ Objectives: This study aims to analyze the influence of Financial Technology and managerial ability on financial performance through technological capital in MSMEs in Surabaya. Method: The study used a quantitative approach with the Structural Equation Modeling method based on Partial Least Square (SEM-PLS). The study population was MSMEs in Surabaya who use Financial Technology services and have business financial records. The sampling technique used accidental sampling. Results/ Findings: The results of the study indicate that Financial Technology does not have a direct significant effect on MSME financial performance, but has a positive and significant effect on technological capital. Managerial ability is also proven to have a positive and significant effect on financial performance and technological capital. In addition, technological capital is proven to have a positive and significant effect on financial performance and is the most dominant variable in this study. The results of the mediation test indicate that technological capital is able to fully mediate the relationship between Financial Technology and financial performance (full mediation) and partially mediate the relationship between managerial ability and financial performance (partial mediation). Conclusions:  This finding indicates that the adoption of financial technology alone is not capable of automatically improving business financial performance.